The circle of rights expands : modern political thought after the Reformation, 1521 (Luther) to 1762 (Rousseau) - Monahan, Arthur P., 1928-2006 (McGill-Queen's studies in the history of ideas, 2007)
Monahan's reading of individual philosophers, including the work of Spinoza, sixteenth-century advocates of religious toleration, and the radical Diggers and Levellers of England in the mid- seventeenth century, constitutes a convincing overview of the political theory of the period.